A four compartment model on human exercise bioenergetics - Sundström, D.; Bäckström, M.; Carlsson, P.; Tinnsten, M. (Procedia Engineering, 2015)
Performance in endurance sports depends on the athlete's ability to generate power output through muscle contraction. The energy requirements of muscles are satisfied by the alactic and lactic bioenergetic pathways, working anaerobically, and the aerobic oxidative phosphorylation of fats and carbohydrates. The aim of this study was to apply further extensions to hydraulic bioenergetic modelling to better describe the regulation of oxidative fuel selection. For this reason, a four compartment bioenergetic model was introduced and regulation of fat and carbohydrate oxidation was implemented. Further regulation was applied to both oxidative fuel selection and anaerobic glycolysis to depend on the current carbohydrate store. The model was formulated mathematically as differential equations, which were solved numerically to perform simulations of human bioenergetics in exercise. Simulation results showed good consistency with experimental findings.